Solidly mounted resonators fabricated for GHz frequency applications based on MgxZn1-xO piezoelectric film. (July 2017) - Liu, Yijian; Shen, Yong; Duan, Franklin; Zhang, Yaozhong; Li, Zhongli; Hwang, Huey-liang; Zhang, Yafei
Abstract: Solidly mounted resonator is a type of film bulk acoustic resonator for microwave operation applications. ZnO piezoelectric films provide a choice to produce solidly mounted resonator, but show a low longitudinal acoustic velocity and a relatively low response. In this work, a ternary compound magnesium doped zinc oxide (Mgx Zn1-x O) piezoelectric film is introduced and investigated, which has a flexible frequency response and a higher acoustic velocity. X-ray diffraction (XRD) θ-2θ coupled scans of the Mgx Zn1-x O films are investigated versus different RF magnetron sputtering deposition conditions. Residual stresses are studied to ensure a reliable fabrication of solidly mounted resonators. A typical device fabricated based on Mgx Zn1-x O piezoelectric film show a resonant frequency at 2.046 GHz with a return loss of −38.9 dB, a quality factor of 965 and a coupling coefficient of 2.5%. The calculated longitudinal acoustic velocity of a Mgx Zn1-x O film is 6854.1 m/s, faster than that of ZnO. Highlights: XRD patterns of the MgxZn1-xO films investigated via changing RF magnetron sputtering deposition conditions. Residual stress also studied to ensure the reliable fabrication of SMR. SMR fabricated based on MgxZn1-xO piezoelectric film shows excellent resonant phenomenon at 2.046 GHz.